The Function of the Brow-Tine in Caribou Antlers - Pruitt, Jr., William O. (ARCTIC, 1966)
Observations of Rangifer tarandus groenlandicus in northern Manitoba and R.t. groenlandicus-granti intergrades in northwest Alaska, show the brow-tine functioning as a protection to the buck caribou's eyes during antler-threshing, also in the forest-tundra region against the stiff twigs of willows. Elsewhere in the arctic and subarctic, the brow-tine sometimes does not develop. The brow-tine is not fully developed until the buck's fourth or fifth year, which marks the onset of the buck's breeding activity.